2022
DOI: 10.1007/s10614-022-10234-w
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Macroeconomics: Lessons Learned from Fourteen Replications

Abstract: I replicate all tables and figures from fourteen papers in Quantitative Macroeconomics, with an emphasis on incomplete market heterogeneous agent models. I report three main findings: (i) all (non-welfare related) major findings of the papers replicate, (ii) welfare findings based on linear approximation methods—1st-order perturbation, linear and log-linearization around steady-state, and linear-quadratic methods—should be treated as quantitatively suspect, (iii) decisions around methods for discretizing exoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…2 Related work Jóhannsson (2009) demonstrated that value iteration could be effectively run in parallel on a GPU soon after the introduction of CUDA. Subsequent research has evaluated the performance of GPU-accelerated value iteration on problems from economics and finance (Aamer et al 2020;Aldrich et al 2011;Duarte et al 2020;Kirkby 2017;Kirkby 2022) and route-finding and navigation (Chen and Lu 2013;Constantinescu et al 2020;Inamoto et al 2011;Ruiz and Hernández 2015). We have only identified a single study that applied this approach to an inventory control problem: Ortega et al (2019) implemented a custom value iteration algorithm in CUDA to find replenishment policies for a subset of perishable inventory problems originally described by Hendrix et al (2019).…”
Section: Introductionmentioning
confidence: 99%
“…2 Related work Jóhannsson (2009) demonstrated that value iteration could be effectively run in parallel on a GPU soon after the introduction of CUDA. Subsequent research has evaluated the performance of GPU-accelerated value iteration on problems from economics and finance (Aamer et al 2020;Aldrich et al 2011;Duarte et al 2020;Kirkby 2017;Kirkby 2022) and route-finding and navigation (Chen and Lu 2013;Constantinescu et al 2020;Inamoto et al 2011;Ruiz and Hernández 2015). We have only identified a single study that applied this approach to an inventory control problem: Ortega et al (2019) implemented a custom value iteration algorithm in CUDA to find replenishment policies for a subset of perishable inventory problems originally described by Hendrix et al (2019).…”
Section: Introductionmentioning
confidence: 99%